UPAYA MENINGKATKAN KETERAMPILAN MOTORIK KASAR ANAK MELALUI PERMAINAN MODIFIKASI BOLA BASKET: EFFORTS TO IMPROVE CHILDREN'S GROSS MOTOR SKILLS THROUGH MODIFIED BASKETBALL GAMES - Dewi, Machfudoh Alfianing; Ratnasih, Tety (Thufuli, 2022)
The purpose of this study was to improve the gross motor skills of group B children at RA Bustanul Aulad. hope each cycle will improve. Gross motor skills are very important for children. because in preschool it has not been maximized, because public facilities are minimal. This research uses classroom action research (CAR). The respondents in the study were preschool B1 graders with 13 people in 2018/2019. The results of data analysis, gross motor skills have an average value of 33.07. very few criteria. The research was conducted before basketball activity. The modified basketball game was carried out by teachers and children. In the first cycle the teacher's activity reached 74.99% with good criteria, in the second cycle it increased to 93.18% with very good criteria. Likewise, the activity of children in the first cycle reached 66.44% with sufficient criteria, in the second cycle it increased to 91.44% with very good criteria. the first cycle of children's gross motor skills obtained an average score of 50.23 with poor criteria and the second cycle increased to 75.30 with good criteria.